Influence of Al concentration and annealing temperature on structural, optical, and electrical properties of Al co-doped ZnO thin films - Gurbuz, Osman; Kurt, Ismail; Caliskan, Serkan; Guner, Sadik (ELSEVIER, 2015)
The pure ZnO and Al-doped ZnO (AZO) thin films (thickness: 200 nm) were prepared on both side polished silica (SiO2) substrates via RF magnetron sputtering at room temperature by using 2.5 inches high-purity ZnO (99.9%) and Al (99.9%) targets. The samples were annealed at 300 degrees C, 400 degrees C and 500 degrees C for 45 min in N-2 ambient in quartz annealing furnace system, respectively. We investigated the effects of various Al concentrations and annealing treatment on the structural, electrical, and optical properties of films. The preferred crystallization was observed along c axis (single (0 0 2) diffraction peak) from substrate surface assigning the single crystalline Wurtzite lattice for pure ZnO and AZO thin films. Although increasing Al concentration decreases the order of crystallization of as-grown films, annealing process increases the long range crystal order. The crystallite sizes vary between minimum 12.98 nm and maximum 20.79 nm for as-grown and annealed samples. The crystallite sizes decrease with increasing Al concentration but increase with increasing annealing temperature as general trend. The grain size and porosity of films change with annealing treatment. The smaller grains coalesce together to form larger grains for many films. However, a reverse behavior is seen for Al2.23ZnO and Al12.30ZnO samples. That is, Al concentration plays critical role as well as temperature on grain size. Low percent optical transmittance (7%) is observed due to higher Al concentration and worse crystal quality for as-grown AZO films. T% decreases until 34.5% for as-grown Al15.62ZnO film. T% increases by increasing annealing temperature. AZO samples annealed at 500 degrees C have around 80% transparencies in the visible range of spectrum. Optical energy band gap values range between 3.17 eV and 3.60 eV for as-grown and annealed samples. Band gap increments are attributed to increasing free electron concentration depending on doped Al ratio known as Burstein-Moss effect. Annealing process increases the band gap values, too. The electrical conductivity and carrier concentration of the films increased with increasing Al content. The mobility decreases due to increase in Al concentration that deteriorates the crystal nature. Annealing process especially at 400 C enables the AZO samples to exhibit best electric conductivity due to long range crystal structured nature and increasing free electron concentration in the films. The maximum electrical conductivity value of 1.06 x 10(4) (Omega cm)(-1) was measured from Al12.30ZnO sample annealed at 400 degrees C. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: AZO; RF magnetron sputtering; Optical and electrical properties; ZINC-OXIDE FILMS; HIGH-TRANSMITTANCE; FABRICATION; DEPOSITION; Chemistry; Materials Science; Physics